Proccedings of 10th International Conference "Environmental Engineering" 2017
DOI: 10.3846/enviro.2017.159
|View full text |Cite
|
Sign up to set email alerts
|

Application of New Technology Data Acquisition Using Aerial (UAV) Digital Images for the Needs of Urban Revitalization

Abstract: The municipal authorities are responsible for carrying out relevant, objective analysis of areas for revitalization, identifying problems and barriers, diagnosis of the causes and determiningthe appropriate range of activities. From the point of view of urban regeneration one of the key issues is to obtain timely and reliable geospatial data. The article presents the possibility of using digital images obtained from the UAV platform to support the urban regeneration process. As part of the research work involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Nakagawa et al (2015) used UAS to inspect a sediment-retarding basin that consisted of dikes, bridges and debris barriers; the study found that UAS is more effective than ground-based scanning. Banaszek et al (2017) used UAS to collect data of various urban structures, in which the UAS data collection approach can replace the laborious and lengthy traditional data update technique. Zhang and Elaksher (2012) studied using UAS to measure surface distresses of unpaved roads and found that comparing to satellites and manned aircrafts, UAS can collect images faster, more safely and cost less.…”
Section: Unmanned Aerial System Applications In Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nakagawa et al (2015) used UAS to inspect a sediment-retarding basin that consisted of dikes, bridges and debris barriers; the study found that UAS is more effective than ground-based scanning. Banaszek et al (2017) used UAS to collect data of various urban structures, in which the UAS data collection approach can replace the laborious and lengthy traditional data update technique. Zhang and Elaksher (2012) studied using UAS to measure surface distresses of unpaved roads and found that comparing to satellites and manned aircrafts, UAS can collect images faster, more safely and cost less.…”
Section: Unmanned Aerial System Applications In Constructionmentioning
confidence: 99%
“…Wang et al (2009) equipped a thermal camera and a visual camera to diagnose both thermal faults and visual faults of the building. Four research articles (Ellenberg et al , 2014a, 2014b; Nakagawa et al , 2015; Perng et al , 2017; Banaszek et al , 2017) applied photogrammetry in their experiments. Researchers have used photogrammetry techniques to generate point cloud data for three-dimensional modeling or distance measurement in applications such as inspecting structural defects (Perng et al , 2017) or detecting building cracks (Ellenberg et al , 2014a, 2014b).…”
Section: On-board Sensors In Unmanned Aerial Systems For Construction Applicationsmentioning
confidence: 99%
“…UAVs are widely used in construction for applications that can be broadly divided into six areas: (1) building inspection, where UAVs are used for data collection to assess the current building condition [19][20][21][22];…”
Section: Uavs For Building Deterioration Detection Currentlymentioning
confidence: 99%
“…An autonomous drone Structural Health Monitoring (SHM) system introduced by Kang and Cha [54] was used for crack detection in concrete and coupled with deep learning techniques. Banaszek et al [55] utilized drones to collect data on various urban structures. Zhang and Elaksher [56] showed that drones could collect images faster, safer, and economical than satellites and manned aircraft in measuring surface distresses of unpaved roads.…”
Section: Infrastructure Monitoring and Photographingmentioning
confidence: 99%